Oil Spill Environmental Forensics Case Studies - Stout, Scott A., editor 359512; Wang, Zhendi, editor 224178; ScienceDirect (Online service) 7722 (Oxford : Butterworth-Heinemann, 2018)
Oil Spill Environmental Forensics Case Studies includes 34 chapters that serve to present various aspects of environmental forensics in relation to “real-world” oil spill case studies from around the globe. Authors representing academic, government, and private researcher groups from 14 countries bring a diverse and global perspective to this volume.